1990
DOI: 10.1128/jvi.64.2.598-606.1990
|View full text |Cite
|
Sign up to set email alerts
|

Feline leukemia virus infection as a potentiating cofactor for the primary and secondary stages of experimentally induced feline immunodeficiency virus infection

Abstract: Preexistent feline leukemia virus (FeLV) infection greatly potentiated the severity of the transient primary and chronic secondary stages of feline immunodeficiency virus (FIV) infection. Of 10 FeLV-FIV carrier cats, 5 died of experimentally induced FIV infection, compared with 2 deaths in 10 cats infected only with FeLV and 1 death in 7 cats infected only with FIV. FIV-infected cats with preexistent FeLV infections developed severe depression, anorexia, fever, diarrhea, dehydration, weight loss, and leukopeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
0
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(53 citation statements)
references
References 52 publications
(44 reference statements)
5
46
0
2
Order By: Relevance
“…Neutropenia is severe (i.e. < 500 cells/~l) in FIV-inoculated neonatal kittens (George et al, 1993) and in cats with pre-existing asymptomatic FeLV infection (Pedersen et al, 1990). Dually infected cats have more severe clinical signs of primary FIV infection and a higher rate of fatal infections and/or gastrointestinal complications.…”
Section: Haematological Disorders Associated With Fivmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutropenia is severe (i.e. < 500 cells/~l) in FIV-inoculated neonatal kittens (George et al, 1993) and in cats with pre-existing asymptomatic FeLV infection (Pedersen et al, 1990). Dually infected cats have more severe clinical signs of primary FIV infection and a higher rate of fatal infections and/or gastrointestinal complications.…”
Section: Haematological Disorders Associated With Fivmentioning
confidence: 99%
“…Histological marrow evaluations during the neutropenic phase of experimental acute FIV infection occasionally reveal myeloid hyperplasia with a shift to immature precursors, lymphoid follicles, and/or marrow lymphocytosis (Pedersen et al, 1990;Beebe et al, 1992;Callanan et al, 1992b, Mandell et al, 1992. However, serial marrow aspirates on a cohort of inoculated cats failed to detect significantly increased frequencies of marrow lymphocytes, plasma cells, or eosinophils when compared to uninfected control cats (Mandell et al, 1992).…”
Section: Haematological Disorders Associated With Fivmentioning
confidence: 99%
“…There are some reports of detection of provirus DNA by the PCR method in HIV infection, and its usefulness (Ou et al, 1988;Albert and Feny6, 1990). Pedersen et al (1990) reported cases in which PCR was used for FIV infection. They used two primer pairs in the gag region of FIV.…”
Section: Detection Of Fiv Proviral Dna In Feline Pbl By Pcrmentioning
confidence: 99%
“…If the single PCR products from the cats in which proviral DNA was not detected are subjected to detection of DNA by Southern blot or dot-blot hybridization using radioisotopes, DNA detection will be more sensitive. Pedersen et al (1990) also detected the PCR products by Southern blot hybridization using radiolabeled probes. However, these procedures are troublesome for routine PCR procedures.…”
Section: Detection Of Fiv Proviral Dna In Feline Pbl By Pcrmentioning
confidence: 99%
“…Virus can be isolated from blood, lymphoid organs, saliva (particularly from clinically ill cats) and cerebrospinal fluid (Pedersen et al, 1987 ;Yamamoto et aL, 1988Yamamoto et aL, , 1989, and grown in vitro in lymphocytes, both T4 and T8 (Pedersen et al, 1987Brown et al, 1991b), macrophages (Brunner & Pedersen, 1989 ;Dow et al, 1990) and astrocytes (Dow et al, 1990 ;Koolen & Egberink, 1990) . Replication occurs best in lymphocytes and macrophages which have been activated or are themselves replicating (Brunner & Pedersen, 1989 ;Pedersen et al, 1990) . In addition, some strains of FIV can also grow in other cell types, for example the feline fibroblast cell line Crfk (Pedersen et al, 1987) .…”
Section: Pathogenesismentioning
confidence: 99%